A role of the 53BP1 protein in genome protection: structural and functional characteristics of 53BP1-dependent DNA repair - Bártová, Eva; Legartová, Soňa; Dundr, Miroslav; Suchánková, Jana (Aging (Albany, NY. Online), 2019)
Nuclear architecture plays a significant role in DNA repair mechanisms. It is evident that proteins involved in DNA repair are compartmentalized in not only spontaneously occurring DNA lesions or ionizing radiation-induced foci (IRIF), but a specific clustering of these proteins can also be observed within the whole cell nucleus. For example, 53BP1-positive and BRCA1-positive DNA repair foci decorate chromocenters and can appear close to nuclear speckles. Both 53BP1 and BRCA1 are well-described factors that play an essential role in double-strand break (DSB) repair. These proteins are members of two protein complexes: 53BP1-RIF1-PTIP and BRCA1-CtIP, which make a "decision" determining whether canonical nonhomologous end joining (NHEJ) or homology-directed repair (HDR) is activated. It is generally accepted that 53BP1 mediates the NHEJ mechanism, while HDR is activated via a BRCA1-dependent signaling pathway. Interestingly, the 53BP1 protein appears relatively quickly at DSB sites, while BRCA1 is functional at later stages of DNA repair, as soon as the Mre11-Rad50-Nbs1 complex is recruited to the DNA lesions. A function of the 53BP1 protein is also linked to a specific histone signature, including phosphorylation of histone H2AX (γH2AX) or methylation of histone H4 at the lysine 20 position (H4K20me); therefore, we also discuss an epigenetic landscape of 53BP1-positive DNA lesions.
Keywords: oprava DNA; Tumor Suppressor p53-Binding Protein 1; buněčné jádro; lidé; Cell Nucleus; fosforylace; 53BP1; DNA Repair; Phosphorylation; Humans